Plant Natural Products as Antimicrobials for Control of Streptomyces scabies: A Causative Agent of the Common Scab Disease - Gutierrez, Justin; Bakke, Amanda; Vatta, Maritza; Merrill, A. Rod (Frontiers in Microbiology, 2022)
The common scab disease caused by Streptomyces scabies, a soil-dwelling Gram-positive bacterium, is an economically important disease of potatoes and other tuber crops. The lack of effective treatments against this disease accounts for large economic losses globally. Plant extracts were screened to find several that effectively inhibited Streptomyces scabies growth in culture. Seven tinctures showed the greatest inhibition of S. scabies growth by reducing pathogen growth in culture by 75% or more. These extracts were myrrh, garlic, cayenne, barberry, frankincense, wild indigo root, and lavender. Myrrh extract from Commiphora myrrha, a resin made from tree sap, showed strong antibacterial activity by reducing the growth of S. scabies to 13% of the control. Additionally, a flavonoid library was screened to identify several compounds that were effective to control the pathogen growth. The flavonoids that showed the greatest inhibition of Streptomyces scabies growth were sophoraflavanone G, jaceosidin, baicalein, and quercetin. Minimum inhibitory concentrations for the effective flavonoids were calculated to be 6.8 ± 0.4 μM, 100.0 ± 2.1 μM, 202.9 ± 5.3 μM, and 285.2 ± 6.8 μM, respectively. The mean lethal doses for these flavonoids against Streptomyces scabies were 2.0 ± 0.1 μM, 22.6 ± 0.5 μM, 52.9 ± 1.3 μM, and 37.8 ± 1.0 μM, respectively. A live/dead assay showed complete cell death in the presence of sophoraflavanone G indicative of a bactericidal mechanism for flavonoid action on Streptomyces scabies. Scanning electron and transmission electron microscopy imaging showed damaged cell membrane morphologies when Streptomyces scabies was exposed to these flavonoids. Mycelia appeared as flat and deflated structures with contents seen as spewing from branching hyphae with numerous holes and tears in the membrane structure indicative of cell death. Sophoraflavanone G showed the greatest potency and potential as a natural antibiotic from the library of tested flavonoids. These results suggest that these plant compounds act on the pathogen through a bactericidal mechanism involving cell membrane destabilization and disruption leading to cell death.